Intelligent Parking Space Control in a System with Reservations - Stepanov, Saša; Šunjka, Zoran; Čabilovski, Đorđe (Promet - Traffic&Transportation, 2019)
The aim of the system with reservations is to reduce the time the user needs to reach the parking space as well as to rationalize the controlling of demands in the central business districts. When applying the system with reservations, it is necessary to know the user’s travel time to the parking space, as well as the time of parking. The sum of these two periods represents the parking space “occupancy”. The purpose of this paper is to suggest a model for determining the total occupancy of a parking space based on 1) the user’s travel time to the parking space; 2) the user’s duration of parking. Considering the fact that we are dealing with values which cannot be exactly estimated, the fuzzy logic system (FLS) is used. A Neural Network (NN) is trained on the basis of data about the estimated values of the input parameters and the real value of output parameters. Thus, a hybrid model of fuzzy logic and neural networks (ANFIS) is obtained. Finally, there is an example based on the real data which shows the application possibilities of this model.